Perceptions of Certified Teachers About The Applying Scientific Approach in Teaching Process - Thomas Pandonge; Ridha Natalia Balol (Sintuwu Maroso Journal of English Teaching, 2021)
The purpose of this study was to determine the perceptions of certification teachers to applying the scientific approach method in the learning process. The method used in study is a qualitative method. Data collection techniques in this study used interviews, observation and documentation. Sources of data in this study are 3 teachers who has been certified. The result of the study show that: (1) Students more active, creative and make the learning process an obligation; (2) The scientific approach many technique, more varied, using many kinds, and (3 make it easier the students for understand. It can be concluded that certified teachers perceptions in applying scientific approach is positive.